2018
DOI: 10.1002/mbo3.748
|View full text |Cite
|
Sign up to set email alerts
|

Roles of end‐binding 1 protein and gamma‐tubulin small complex in cytokinesis and flagella formation of Giardia lamblia

Abstract: Giardia lamblia is a unicellular organism with two nuclei, a median body, eight flagella, and an adhesive disk. γ‐Tubulin is a microtubule (MT)‐nucleating protein that functions in the γ‐tubulin small complex (γ‐TuSC) in budding yeast. In this study, G. lamblia γ‐tubulin (Glγ‐tubulin) was found to bind to another MT‐binding protein, namely G. lamblia end‐binding protein 1 (GlEB1), via both in vivo and in vitro assays. Hemagglutinin (HA)‐tagged Glγ‐tubuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…, 2014 ). Intriguingly, EB1 knockdown in Giardia has been shown to reduce median body volume, flagella length, and cause loss of axoneme central pairs ( Kim and Park, 2019 ). Although less severe, these phenotypes are similar to what we observe in Nek8445-depleted cells.…”
Section: Discussionmentioning
confidence: 99%
“…, 2014 ). Intriguingly, EB1 knockdown in Giardia has been shown to reduce median body volume, flagella length, and cause loss of axoneme central pairs ( Kim and Park, 2019 ). Although less severe, these phenotypes are similar to what we observe in Nek8445-depleted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Localization of GlPLK at basal bodies, which function as an MTOC, indicated that GlPLK might play a role in MT nucleation. A previous study demonstrated that depletion of the γ-tubulin ring complex (γ-TuSC) affects MT nucleation, resulting in shortening of the agella [17]. Overexpression of dominantnegative mutant kinesin-13, a motor protein, produced Giardia with longer agella and defective mitotic spindles [40].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of HAtagged GlPLK was con rmed by western blotting. Giardia trophozoites carrying pΔ.pac [17] were included as a control.…”
Section: Construction Of G Lamblia Expressing Ha Epitope-tagged Glplmentioning
confidence: 99%
See 2 more Smart Citations